Porous coordination polymer, preparation method thereof and application of porous coordination polymer in C3H6 / C3H8 mixed gas separation
By designing the porous coordination polymer [Zn(MeOipa)(bpe)]n, it uses its unique one-dimensional corrugated pore structure to achieve efficient selective separation of propylene and propane, solving the problems of high energy consumption and high equipment costs in the traditional method, and achieving high purity propylene separation with low energy consumption.
Patent Information
- Application Number
- CN202510589427.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-05-08
AI Technical Summary
It is difficult for the prior art to efficiently separate the mixed gas of propylene and propane under low energy consumption. The traditional method has problems such as high energy consumption, high equipment costs and impurities introduction.
Using the porous coordination polymer [Zn(MeOipa)(bpe)]n, a unique one-dimensional corrugated pore structure is formed through the coordination between the metal zinc center and a specific organic ligand, and the electronegative oxygen atoms and nitrogen atoms on the pore surface are selectively adsorbed propylene and propane.
It realizes efficient separation of propylene and propane at room temperature and pressure, has high selectivity and adsorption capacity, good material stability, low energy consumption, simple operation, and small equipment investment. It is suitable for high-purity propylene separation of important industrial gas mixtures.
Smart Images

Figure CN120248362A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials for efficient separation of propylene / propane gas in industrial mixed gases, and in particular to a porous coordination polymer, a preparation method thereof, and an application thereof in the separation of propylene / propane mixed gas. Background Art
[0002] Propylene (C3H6) is an important petrochemical raw material for the production of polypropylene, and propylene purity higher than 99.5% is required. The separation of propylene (C3H6) and propane (C3H8) in industry is mainly accomplished by energy-intensive cryogenic distillation. However, its sustainable development is hindered by corrosion, degradation, harmful by-product emissions, and a large demand for thermal energy, and it is also prone to introducing additional impurities such as solvent vapors. Cryogenic distillation needs to be carried out in a very tall distillation column, and there are problems such as energy-intensive at low temperature and high pressure and high cost. Therefore, this has prompted chemists to develop porous materials with lower energy consumption for the adsorption separation of propylene / propane.
[0003] In recent years, the use of porous materials as adsorbents for the adsorption separation of light hydrocarbon gas mixtures has received increasing attention due to their high efficiency, easy operation, low energy consumption, etc. Among them, porous coordination polymer materials, also known as metal-organic framework materials, are three-dimensional porous materials with a periodic network structure, composed of inorganic metal ions (or metal clusters) and organic ligands. They have unique properties such as a large specific surface area, a structure that can be carefully designed, and excellent gas adsorption performance, and can be customized to have pore sizes and functions suitable for separating target gases from mixtures. However, due to the highly similar physical properties and molecular sizes of C3H6 and C3H8 gases, the boiling point of propylene (C3H6) (225.46 K) and molecular size (6.44×4.65×4.16 Å 3 ), the boiling point of propane (231.02 K) and molecular size (C3H8) (6.61×4.52×4.02 Å 3 ), it is still a challenging task to precisely construct a physical adsorbent with suitable pores for the separation of propylene / propane mixed gas.
[0004] Therefore, there is an urgent need to develop a porous coordination polymer material adsorbent with low cost, simple preparation, low energy consumption, and high selectivity for separating propylene / propane gas mixtures. Summary of the Invention
[0005] To solve the above technical problems, the present invention provides a porous coordination polymer, a preparation method thereof, and an application thereof in the separation of propylene / propane mixed gas. The present invention can efficiently separate high-purity C3H6 gas from a typical propylene / propane gas mixture, can be implemented under ambient conditions of normal temperature and pressure, has advantages such as simple and mild operating conditions, low energy consumption, small equipment investment, recyclability of materials, etc., and has high C3H6 adsorption selectivity. The effective separation of high-purity C3H6 from the important industrial gas mixture propylene / propane has important application prospects in solving energy security and high energy consumption and low efficiency in traditional industrial gas separation, etc.
[0006] The first object of the present invention is to provide a porous coordination polymer, and the structural formula of the porous coordination polymer is [Zn(M)(N)] n , where M is a first organic ligand containing multiple carboxyl groups, N is a second organic ligand containing multiple nitrogens; n indicates that the porous coordination polymer is an infinitely extended material, and Zn(M)(N) represents the minimum structural unit.
[0007] Among them, the metal zinc center in the porous coordination polymer is tetracoordinated, and is coordinated by two oxygens on the carboxyl group of the first organic ligand and two nitrogens in the second organic ligand.
[0008] In some embodiments of the present invention, the porous coordination polymer is a three-dimensional structure with multiple interpenetrations and has a three-dimensional structure with one-dimensional corrugated pores; The porous coordination polymer belongs to the orthorhombic system, space group: Pbcn, and the unit cell parameters are a = 23.2481(6) Å, b = 10.1771(2) Å, c = 19.6694(4) Å, alpha = 90, beta = 90, gamma = 90; The pore size of the pore channel of the porous coordination polymer is 4.8 Å × 4.8 Å; One or more of electronegative oxygen atoms, nitrogen atoms, methoxy groups, and uncoordinated oxygen atoms are distributed on the surface of the pore channel of the porous coordination polymer.
[0009] In some embodiments of the present invention, the first organic ligand includes one or more of 5-methoxy-1,3-benzenedicarboxylic acid, 5-methyl-1,3-benzenedicarboxylic acid, and 1,3-benzenedicarboxylic acid; the second organic ligand includes one or more of 1,2-bis(4-pyridyl)ethane, 1,2-bis(4-pyridyl)ethylene, and 1,2-bis(4-pyridyl)acetylene.
[0010] Furthermore, the chemical formula of the porous coordination polymer is [Zn(MeOipa)(bpe)] n, Zn represents the metal zinc center, MeOipa represents the organic ligand 5-methoxy-1,3-benzenedicarboxylic acid, and the structural formula is , bpe represents the organic ligand 1,2-bis(4-pyridyl)ethane, and the structural formula is .
[0011] The second object of the present invention is to provide a preparation method of the porous coordination polymer, including the following steps: Dissolve the zinc source, the first organic ligand and the second organic ligand in an organic solvent to obtain a mixed solution, and heat-treat the mixed solution to obtain a crystal material; Wash the crystal material and perform a solvent exchange treatment in a low-boiling solvent to remove the solvent molecules in the pores of the crystal material to obtain a porous crystal material; Heat-activate the porous crystal material to obtain the porous coordination polymer.
[0012] In some embodiments of the present invention, the zinc source is selected from one or more of Zn(NO3)2, Zn(CH3COO)2, and ZnSO4; one or more of 5-methoxy-1,3-benzenedicarboxylic acid, 5-methyl-1,3-benzenedicarboxylic acid, and 1,3-benzenedicarboxylic acid; the second organic ligand includes one or more of 1,2-bis(4-pyridyl)ethane, 1,2-bis(4-pyridyl)ethylene, and 1,2-bis(4-pyridyl)acetylene; The low-boiling solvent includes methanol.
[0013] The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, and diethyl ether.
[0014] In some embodiments of the present invention, the molar ratio of the second organic ligand, the first organic ligand and the zinc source is 1:(0.1~10):(0.1~10).
[0015] In some embodiments of the present invention, the conditions of the heat treatment: the heating temperature is 80-100 °C, and the heating time is 24~48 h; The conditions of the heat activation: under a vacuum condition at a temperature of 100~150 °C, heat for 24~48 h.
[0016] The third object of the present invention is to provide a physical adsorbent material, including the porous coordination polymer.
[0017] The fourth object of the present invention is to provide the application of the physical adsorbent material in separating the mixed gas of C3H6 and C3H8.
[0018] In some embodiments of the present invention, the volume ratio of C3H6 to C3H8 in the mixed gas is 1:99 to 99:1; The physical adsorbent material selectively adsorbs C3H6 gas molecules and excludes C3H8 gas molecules at normal temperature and pressure.
[0019] The above technical solution of the present invention has the following advantages compared with the prior art: (1) The organic ligand 5-methoxy-1,3-benzenedicarboxylic acid designed and synthesized in the present invention is a polycarboxylic acid that can coordinate and extend at both ends. Another organic ligand 1,2-bis(4-pyridyl)ethane has two pyridine N atoms, which can participate in coordination in two directions respectively, and can self-assemble with the metal zinc center into a porous coordination polymer. The prepared porous coordination polymer [Zn(MeOipa)(bpe)] n is coordinated by the metal zinc center and the organic ligand. The metal zinc center is tetracoordinated. Among them, the metal zinc center coordinates with two oxygen atoms on the carboxyl group of the organic ligand 5-methoxy-1,3-benzenedicarboxylic acid. There are two oxygen atoms on the carboxyl group of the organic ligand 5-methoxy-1,3-benzenedicarboxylic acid that are not coordinated. In addition, each metal zinc center coordinates with two nitrogens of the organic ligand 1,2-bis(4-pyridyl)ethane, forming a three-dimensional structure with multiple interpenetrations and a three-dimensional structure with one-dimensional corrugated pores.
[0020] (2) The [Zn(MeOipa)(bpe)] provided by the present invention n has a unique high-porosity structure, a multiple interpenetration structure, and periodic one-dimensional corrugated pores. The pore size of the pores is 4.8 Å×4.8 Å. The pore surface is distributed with abundant electronegative oxygen atoms, nitrogen atoms and methoxy groups, including the uncoordinated oxygen atoms from 5-methoxy-1,3-benzenedicarboxylic acid. Its pore structure and size are easy for C3H6 gas to diffuse and limit the diffusion of C3H8 gas, showing a high adsorption capacity and adsorption selectivity for C3H6. In addition, the material has extremely high stability, and the thermal decomposition temperature is about 270 °C.
[0021] (3) Compared with traditional porous material adsorbents (such as zeolites, activated carbon, etc.), the porous coordination polymer material used in the present invention has a special one-dimensional corrugated pore structure and precisely designed pore sizes, which are conducive to the diffusion of C3H6 gas while restricting the diffusion of C3H8 gas. This material has a specific recognition and adsorption ability for C3H6 molecules, can exclude and adsorb C3H8 gas, and can efficiently and selectively capture C3H6 gas to achieve efficient purification and separation. The gas adsorption ratios (Uptake Ratio) of equimolar propylene / propane mixed gas at room temperatures of 273 K, 298 K, and 303 K are 41.7, 7.1, and 5.4 respectively; the IAST gas selectivities of equimolar propylene / propane mixed gas at room temperatures of 298 K and 303 K are >1.66×10 5 and ~1.40×10 3 . In addition, this material has the advantages of high adsorption capacity, excellent desorption performance, and can be recycled repeatedly. It is easy to synthesize, with simple, safe operation, high yield and basically no by-products in preparation.
[0022] (4) The method for separating propylene / propane mixed gas provided by the present invention, compared with the traditional propylene / propane separation technologies of solvent extraction and cryogenic distillation (which have disadvantages such as corrosion, harmful by-product emissions, large energy consumption requirements, and high costs), can be implemented under ambient conditions of normal temperature and pressure. It has the advantages of simple and mild operating conditions, low energy consumption, small equipment investment, and recyclable materials, and has high propylene / propane separation selectivity. It is expected to effectively separate high-purity C3H6 from the important industrial gas mixture of propylene / propane, and has important application prospects in solving energy security and high energy consumption and low efficiency in traditional industrial gas separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to make the content of the present invention easier to be clearly understood, the following further details the present invention according to specific embodiments of the present invention in combination with the drawings, where Figure 1 is a schematic diagram of the crystal coordination structure and pore structure obtained after the crystal material of [Zn(MeOipa)(bpe)] obtained in Example 1 is tested and analyzed by single crystal X-ray diffraction; where a and b are observed from the angles of the a-axis and b-axis of the unit cell respectively. n
[0024] Figure 2 is the X-ray powder diffraction experimental result of [Zn(MeOipa)(bpe)] obtained in Example 1; n Figure 3 is the thermogravimetric curve of [Zn(MeOipa)(bpe)] obtained in Example 1 n before and after vacuum activation; Figure 4The activated [Zn(MeOipa)(bpe)] obtained in Example 1 n Adsorption isotherms of C3H6 and C3H8 at 273 K and 1 bar; Figure 5 The activated [Zn(MeOipa)(bpe)] obtained in Example 1 n Adsorption isotherms of C3H6 and C3H8 at 298 K and 1 bar; Figure 6 The activated [Zn(MeOipa)(bpe)] obtained in Example 1 n Results of X-ray powder diffraction experiments before and after the adsorption isotherm test; Figure 7 The activated [Zn(MeOipa)(bpe)] obtained in Example 1 n IAST gas selectivity of propylene / propane with different molar ratios of 50:50, 10:90, and 1:99 at 298 K and 1 bar; Figure 8 The scaled-up synthesis of [Zn(MeOipa)(bpe)] obtained in Example 2 n Results of X-ray powder diffraction experiments; Figure 9 The activated [Zn(MeOipa)(bpe)] obtained in Example 2 n Adsorption isotherms of C3H6 and C3H8 at 303 K and 1 bar; Figure 10 The activated [Zn(MeOipa)(bpe)] obtained in Example 2 n IAST gas selectivity of propylene / propane with different molar ratios of 50:50, 10:90, and 1:99 at 303 K and 1 bar.
[0025] Figure 11 For [Zn(MeOipa)(bpe)] in Example 2 n And the comparison results of IAST selectivity with Co-aip-pyz, NTU-85, HIAM-301, and TYUT-23 in the prior art. Detailed implementation mode
[0026] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, so that those skilled in the art can better understand the present invention and be able to implement it, but the embodiments given are not intended to limit the present invention.
[0027] Example 1: This example provides a preparation method of a porous coordination polymer for separating propylene / propane mixture gas, which is specifically as follows: 1. Preparation of the material: Weigh 29.7 mg of Zn(NO3)2·6H2O, 18.4 mg of the organic ligand 1,2-bis(4-pyridyl)ethane (bpe), and 18.0 mg of the organic ligand 5-methoxy-1,3-benzenedicarboxylic acid (MeOipa) and add them separately to 9 mL of a mixed solvent of N,N-dimethylformamide / ultrapure water (volume ratio 6:3). After ultrasonic treatment for 5 min, a clear solution is obtained. Subsequently, transfer the above solution to a glass reaction flask with a screw cap and heat it to 90 °C in an oven and maintain for 24 h. After the reaction is completed, filter using a 0.22 μm organic filter membrane and wash the precipitate 3 times with 15 mL of N,N-dimethylformamide and 15 mL of methanol. Immerse the obtained material in methanol for a 5-day solvent exchange, changing the methanol 2 times a day, with 10 mL of methanol used each time. Finally, heat it to 100 °C in a vacuum oven and activate for 24 h to obtain the activated [Zn(MeOipa)(bpe)] n .
[0028] 2. Characterization of the material: a. Use single-crystal X-ray diffraction to test and analyze the crystal structure and pore structure schematic diagram of the synthesized [Zn(MeOipa)(bpe)] n . The results are as Figure 1 shown: The obtained material is a multiple interpenetrating structure with periodic one-dimensional corrugated pores.
[0029] b. Analyze the synthesized material using X-ray powder diffraction. The results are consistent with the powder diffraction obtained by simulating the resolved structure. The results are as Figure 2 shown: The powder diffraction of the activated material is consistent with that of the material before activation (the freshly synthesized material), indicating that the material has structural thermal stability and maintains a stable structure after solvent removal. The thermogravimetric curves of the material before and after vacuum drying (as Figure 3 shown) indicate that the structure of the material is stable after activation at 100 °C under vacuum drying.
[0030] c. Test the adsorption isotherms of C3H6 and C3H8 by the activated [Zn(MeOipa)(bpe)] n at 273 K. The results are as Figure 4 shown. The saturated adsorption capacity of the activated [Zn(MeOipa)(bpe)] n adsorbent material for C3H6 is significantly higher than that for C3H8, and it shows a molecular sieve size exclusion effect on C3H8, indicating that [Zn(MeOipa)(bpe)] n has a significant preferential selective adsorption ability for C3H6. In addition, due to the molecular sieve effect, there is a hysteresis phenomenon in desorption.
[0031] d. The activated [Zn(MeOipa)(bpe)] was tested n for the adsorption isotherms of C3H6 and C3H8 at 298 K. The results are as Figure 5 shown. The saturated adsorption capacity of the activated [Zn(MeOipa)(bpe)] n adsorbent material for C3H6 is significantly higher than that for C3H8, and it shows a molecular sieve exclusion effect on C3H8, indicating that [Zn(MeOipa)(bpe)] n has the ability to preferentially and selectively adsorb C3H6 under the room temperature environment conditions of 298 K / 1 bar; in addition, due to the molecular sieve effect, there is a hysteresis phenomenon in desorption.
[0032] e. The X-ray powder diffraction patterns of the activated [Zn(MeOipa)(bpe)] n before and after the adsorption isotherm test are consistent (as Figure 6 shown), indicating that the activated [Zn(MeOipa)(bpe)] n has structural stability before and after the adsorption test. The gas uptake ratios of equimolar propylene / propane mixtures at room temperatures of 273 K and 298 K are 41.7 and 7.1 respectively; the IAST gas selectivities of propylene / propane mixtures with gas molar ratios of 50:50, 10:90, and 1:99 at room temperature of 298 K are >1.66×10 5 , >5.5×10 4 and >5.5×10 3 respectively (as Figure 7 shown). This example shows that [Zn(MeOipa)(bpe)] n has excellent selective separation ability for propylene / propane under the room temperature environment conditions of 298 K / 1 bar.
[0033] Example 2: This example is a 10-fold volume amplification synthesis of Example 1, specifically as follows: 1. Preparation method of materials: Weigh 594 mg of Zn(NO3)2·6H2O (to promote the full reaction of the ligand, the molar concentration ratio of Zn(NO3)2·6H2O is also increased to 2 times that of bpe), 184 mg of bpe, and 180 mg of MeOipa are respectively added to 90 mL of a mixed solvent of N,N-dimethylformamide / ultrapure water (volume ratio of 6:3). After ultrasonic treatment for 5 min, a clear solution is obtained. Subsequently, the above solution is transferred to a glass bottle with a screw cap and heated to 80 °C in an oven and maintained for 48 h (as Figure 8As shown). After the reaction, it was filtered using a 0.5 μm organic filter membrane, and the precipitate was washed 3 times with 50 mL of N,N-dimethylformamide and 50 mL of methanol. The obtained material was immersed in methanol for a 4-day solvent exchange, with methanol being changed 2 times a day, 50 mL of methanol each time. Finally, it was heated to 150 °C in a vacuum oven and activated for 48 h to obtain activated [Zn(MeOipa)(bpe)] n .
[0034] 1. Characterization of the material: The synthesized material was analyzed using X-ray powder diffraction, and the results were consistent with the powder diffraction obtained from the simulated resolved structure (as Figure 8 shown). The powder diffraction of the activated material was consistent with that of the material before activation (as Figure 8 shown), indicating that the material has structural thermal stability and maintains a stable structure after solvent removal.
[0035] The adsorption isotherms of C3H6 and C3H8 at 303 K for the activated [Zn(MeOipa)(bpe)] n were tested, and the results are as Figure 9 shown. The saturated adsorption capacity of the activated [Zn(MeOipa)(bpe)] n adsorbent material for C3H6 was significantly higher than that for C3H8, and it showed a molecular sieve exclusion effect for C3H8, indicating that [Zn(MeOipa)(bpe)] n has a preferential selective adsorption ability for C3H6. In addition, due to the molecular sieve effect, there is a hysteresis phenomenon in desorption.
[0036] The gas adsorption ratio (Uptake Ratio) of an equimolar propylene / propane mixture at room temperature of 303 K was 5.4; the IAST gas selectivity of propylene / propane mixtures with gas molar ratios of 50:50, 10:90, and 1:99 at room temperature of 303 K was ~1.40×10 3 , ~1.40×10 3 and ~1.23×10 3 (as Figure 10 shown). This example shows that [Zn(MeOipa)(bpe)] n can be easily synthesized on a large scale and has excellent propylene / propane selective separation ability.
[0037] Comparing with the previously reported benchmark materials such as Co-aip-pyz, NTU-85, HIAM-301, TYUT-23 (as Figure 11 shown), the propylene / propane separation selectivity of [Zn(MeOipa)(bpe)] n is significantly higher.
[0038] Obviously, the above embodiments are merely examples given for clear illustration and are not limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all the implementation manners here. And the obvious changes or modifications derived therefrom still fall within the protection scope of the present invention.
Claims
1. A porous coordination polymer, characterized in that, The structural formula of the porous coordination polymer is [Zn(M)(N)] n , where M is a first organic ligand containing multiple carboxyl groups, and N is a second organic ligand containing multiple nitrogens; Among them, the metal zinc center in the porous coordination polymer is tetracoordinated, which is coordinated by two oxygen atoms on the carboxyl group of the first organic ligand and two nitrogen atoms in the second organic ligand; the porous coordination polymer is a three-dimensional structure with multiple interpenetrations and has a three-dimensional structure with one-dimensional corrugated pores.
2. The porous coordination polymer according to claim 1, wherein The porous coordination polymer belongs to the orthorhombic crystal system, space group: Pbcn, and the unit cell parameters are a = 23.2481(6) Å, b = 10.1771(2) Å, c = 19.6694(4) Å, alpha = 90, beta = 90, gamma = 90; The pore size of the pore channels of the porous coordination polymer is 4.8 Å × 4.8 Å; One or more of electronegative oxygen atoms, nitrogen atoms, methoxy groups, and uncoordinated oxygen atoms are distributed on the surface of the pore channels of the porous coordination polymer.
3. The porous coordination polymer according to claim 1, characterized in that, The first organic ligand includes one or more of 5-methoxy-1,3-benzenedicarboxylic acid, 5-methyl-1,3-benzenedicarboxylic acid, and 1,3-benzenedicarboxylic acid; the second organic ligand includes one or more of 1,2-bis(4-pyridyl)ethane, 1,2-bis(4-pyridyl)ethylene, and 1,2-bis(4-pyridyl)acetylene.
4. A method for preparing a porous coordination polymer as described in any one of claims 1 to 3, characterized in that, It includes the following steps: Dissolve a zinc source, a first organic ligand, and a second organic ligand in an organic solvent to obtain a mixed solution, and perform heat treatment on the mixed solution to obtain a crystal material; Wash the crystal material and perform solvent exchange treatment in a low-boiling solvent to remove solvent molecules in the pore channels of the crystal material to obtain a porous crystal material; Perform heat activation treatment on the porous crystal material to obtain the porous coordination polymer.
5. The preparation method according to claim 4, characterized in that, The zinc source is selected from one or more of Zn(NO3)2, Zn(CH3COO)2, and ZnSO4; The first organic ligand includes one or more of 5-methoxy-1,3-benzenedicarboxylic acid, 5-methyl-1,3-benzenedicarboxylic acid, and 1,3-benzenedicarboxylic acid; The second organic ligand includes one or more of 1,2-bis(4-pyridyl)ethane, 1,2-bis(4-pyridyl)ethylene, and 1,2-bis(4-pyridyl)acetylene; The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, and diethyl ether.
6. The preparation method according to claim 4, characterized in that, The molar ratio of the second organic ligand, the first organic ligand, and the zinc source is 1:(0.1~10):(0.1~10).
7. The preparation method according to claim 4, characterized in that, The conditions for the heat treatment: the heating temperature is 80 - 100 °C, and the heating time is 24~48 h; The conditions for the heat activation: under a vacuum condition at a temperature of 100~150 °C, heat for 24~48 h.
8. A physical adsorbent material, characterized in that, It includes the porous coordination polymer according to any one of claims 1~3.
9. Application of the physical adsorbent material according to claim 8 in separating a mixed gas of C3H6 and C3H8.
10. The application according to claim 9, wherein The volume ratio of C3H6 and C3H8 in the mixed gas is 1:99~99:1; The physical adsorbent material selectively adsorbs C3H6 gas molecules and excludes C3H8 gas molecules at normal temperature and pressure.
Citation Information
Patent Citations
Metal complex, adsorbent, separating material, and 1, 3-butadiene separation method
CN105283445A
Coordination polymer material as well as preparation method and application thereof
CN116120573A
Mixed-ligand metal-organic frameworks with large pores
KR1020100029685A
Conductivity enhancement of mofs via development of mofpolymer composite material
US20200291045A1